Charge‐Compensated Compound Defects in Ga‐containing Thermoelectric Skutterudites. (6th February 2013) - Qiu, Yuting; Xi, Lili; Shi, Xun; Qiu, Pengfei; Zhang, Wenqing; Chen, Lidong; Salvador, James R.; Cho, Jung Y.; Yang, Jihui; Chien, Yuan‐chun; Chen, Sinn‐wen; Tang, Yinglu; et al.
Abstract Heavy doping changes an intrinsic semiconductor into a metallic conductor by the introduction of impurity states. However, Ga impurities in thermoelectric skutterudite CoSb3 with lattice voids provides an example to the contrary. Because of dual‐site occupancy of the single Ga impurity charge‐compensated compound defects are formed. By combining first‐principle calculations and experiments, we show that Ga atoms occupy both the void and Sb sites in CoSb3 and couple with each other. The donated electrons from the void‐filling Ga (GaVF) saturate the dangling bonds from the Sb‐substitutional Ga (GaSb). The stabilization of Ga impurity as a compound defect extends the region of skutterudite phase stability toward Ga0.15Co4Sb11.95 whereas the solid–solution region in other directions of the ternary phase diagram is much smaller. A proposed ternary phase diagram for Ga‐Co‐Sb is given. This compensated defect complex leads to a nearly intrinsic semiconductor with heavy Ga doping in CoSb3 and a much reduced lattice thermal conductivity (κL) which can also be attributed to the effective scattering of both the low‐ and high‐frequency lattice phonons by the dual‐site occupant Ga impurities. Such a system maintains a low carrier concentration and therefore high thermopower, and the thermoelectric figure of merit quickly increases to 0.7 at a Ga doping content as low as 0.1 per Co4Sb12 and low carrier concentrations on the order of 1019 cm−3.